Is there an association with spino-pelvic relationships and clinical outcome of type a thoracic and lumbar fractures treated non-surgically? - Joaquim, Andrei Fernandes; Rodrigues, Sérgio Augusto [UNESP]; da Silva, Felipe Soares; da silva, Otávio Turolo; Ghizoni, Enrico; Tedeschi, Helder; Schroeder, Gregory D.; Vaccaro, Alexander R.; Patel, Alpesh A. (International Journal of Spine Surgery, 2018)
Background: The objective was to evaluate if there is an association of the spino-pelvic relationships and the global spinal alignment with the outcome of AO type A injuries treated nonsurgically. Methods: This is a retrospective case series. Patients treated nonsurgically for AOSpine type A fractures (T1-L5) with at least 1 year follow-up identified. A standing antero-posterior and lateral 36-inch radiographs and measures of spino-pelvic relationships and sagittal alignment were obtained, as well as clinical assessment using the visual analog scale, the Short-Form 36 (SF-36) questionnaire, the Oswestry Disability Index (ODI), and labor status. Results: Twenty-two patients with 33 fractures were included (L1 was the most injured level with 18.2%). There were 17 men (77.2%) and the mean age was 47.1 years. Follow-up ranged from 12 to 60 months (mean of 27.8 months). There were 22 type A1 (66.7%), 3 type A2 (9%), 6 type A3 (18%), and 2 type A4 (6%) fractures. The ODI ranged from 4% to 58%, with a mean of 24.4%. The SF-36 physical health score ranged from 23 to 82.25 (mean 49.59), and the mental health score ranged from 14.75 to 94.25 (mean 63.28). No association was identified between the spino-pelvic measurements, global alignment, and patient-reported outcomes. Conclusions: Type A fractures had a clinically relevant amount of long-term disability even when surgical treatment is not required. Spino-pelvic relationships and final global spinal alignment did not associate with outcome measurements.
Keywords: Burst; Compression; Conservative treatment; Fractures; ODI; Outcome; Sagittal balance; SF-36; Spinopelvic relationships; Thoracolumbar; TLICS; VAS